Concentrations of Zn, Mn and Al in wood chips from wood-based manufacturing industries. Issue 1 (1st May 2022) - Ayob, S; Othman, N; Altowayti, W A H
Abstract: The elemental composition of wood chip samples manufactured in the wood industries at Batu Pahat were analyzed for their heavy metals composition. This study was aimed to prove that heavy metals can accumulate in wood and trees themselves without adding any wood treatment additives. ICP-MS analysis was conducted on the wastewater at the same manufacturing industry to evince the occurrence of the leaching process that causes the presence of heavy metals in the wastewater. The results of the experiments showed that Mn, Zn and Al were among the highest metal traces found in the wood chips. As a result, Mn concentrations in three different samples of wood chips were 83.6 mg/L, 88.1 mg/L, and 80.9 mg/L, whereas Zn amounts were 38.8 mg/L, 40.2 mg/L, and 37.7 mg/L. Furthermore, the amounts of Al traces in the three samples were 28.2 mg/L, 29.6 mg/L, and 30.7 mg/L, respectively. The study also found that the highest metal trace in wastewater shows a proportional value to the highest concentration of heavy metals in wood chips. Therefore, it can be concluded that, even though the whole chipping production process is considered to be a dry process, the wastewater generated after cleaning surfaces, storage tanks and machinery, causes heavy metal leaching and contributes to the presence of heavy metals in wastewater.